High Glycemic Index Foods Increase Oxidative Stress and Cause Chronic Musculoskeletal Pain - Adinda; Legiran; Arwan Bin Laeto (Sriwijaya Journal of Medicine, 2024)
Chronic musculoskeletal pain is a widespread condition that impacts quality of life and poses significant health care challenges. Recent research shows that dietary factors, especially the consumption of high glycemic index (GI) foods, play an important role in exacerbating musculoskeletal pain through metabolic and inflammatory pathways. High GI foods cause a rapid spike in blood glucose, which causes increased production of reactive oxygen species (ROS) resulting in oxidative stress. Oxidative stress disrupts normal cellular function, increases the production of pro-inflammatory cytokines, and exacerbates chronic inflammation, a major driver of musculoskeletal pain. This review discusses the mechanisms by which high GI foods increase oxidative stress and contribute to the onset and persistence of chronic musculoskeletal pain and discusses oxidative damage increasing degradation of musculoskeletal tissue, delaying recovery, and worsening pain perception. Previous studies linking high GI diets to increased oxidative stress and the incidence of musculoskeletal pain provide evidence of the potential for dietary modification as a non-invasive therapeutic strategy. In conclusion, reducing foods with a high glycemic index and adopting a diet rich in antioxidants and low glycemic index to reduce oxidative stress and inflammation is very necessary. Understanding the impact of diet on oxidative stress offers a promising avenue for the prevention and treatment of chronic musculoskeletal pain. Further research is needed to strengthen this association and develop targeted dietary interventions for CMP patients.